Developing Two Culture of Health Measurement Tools: Examining Employers' Efforts to Influence Population Health Inside and Outside Company Walls. Issue 12 (December 2018) - Kent, Karen B.; Goetzel, Ron Z.; Roemer, Enid Chung; McCleary, Katherine; Henke, Rachel Mosher; Head, Michael A.; Fabius, Raymond
Abstract : Objective: The aim of the study was to develop tools that quantify employers' investment in building cultures of health (COH)—inside and outside company walls. Methods: Two COH instruments were developed through literature reviews and expert consultation. The first focused on internal culture of health (COH-INT), that is, programs, policies, and attributes of the physical and social environments that support employees' health and well-being. The second focused on external culture of health (COH-EXT), that is, programs, policies, and environmental supports that promote communities ' health. We administered these tools to 32 employers and examined instrument reliability, distribution of scores, and correlation between the two instruments. Results: Both tools demonstrated adequate reliability. COH-EXT scores changed minimally over the 3-year study timeframe. There was little correlation between the COH-INT and COH-EXT scores. Conclusions: More research is needed to further develop and validate COH-EXT instruments. Abstract : Supplemental Digital Content is available in the text